Comparação de duas técnicas de moldagem para confecção de prótese total em pacientes com rebordo mandibular severamente reabsorvido : estudo clínico cego randomizado controlado - Albuquerque, Ivo de Souza (2018)
While quality scientific evidence regarding the simplified technique for complete denture fabrication is being built, a deeper understanding of aspects such as the elimination of a twostep impression technique for treatment success, as well as whether application is possible for patients with extremely resorbed jaws is of clinical interest. Thus, the objective of this study was to evaluate, by means of a randomized controlled clinical trial, the influence of the secondary impression on rehabilitation of complete edentulous patients presenting extremely resorbed jaws on oral health related quality of life (OHRQoL), denture satisfaction, denture quality, masticatory ability and performance, as well as post-delivery adjustments required. The sample was composed by complete edentulous patients requesting treatment with upper and lower dentures. The participants were randomly allocated into two groups: MU (n=25) received prostheses obtained without secondary impression, and MD (n=25), dentures fabricated by means of a two-step impression technique with individual trays, border molding for peripheral sealing by means of compound, and polyether moulding for inner surface). Before treatment, 3 and 6 months after denture delivery, OHRQoL was evaluated by means of the questionnaire OHIP-EDENT, masticatory ability and denture general satisfaction, as well as in various specific aspects of the mandibular prosthesis, by means of validated questionnaires. A color changeable chewing gum test was used to evaluate masticatory performance. Also, it was assessed post-delivery adjustments required, and denture clinical quality by a blind prosthodontist as well. Groups were compared by appropriate tests accordingly to data distribution (α=5%). Intergroup differences regarding OHRQoL only occurred in the assessment of 3 months (p=0.037), not persisting in the second evaluation (p=0.072). The two groups were similar regarding denture quality (p=0.760), masticatory performance (3 months: p=0.524; 6 months: p=0.424), number of sessions required for postdelivery adjustments in mandibular prosthesis (p=0.183), overall denture satisfaction, and masticatory hability (p>0.05). It was concluded that a simplified method of denture impression is capable of producing complete denture of good quality comparable to those fabricated by conventional techniques, influencing OHRQoL, denture satisfaction, masticatory and performance ability of its users in a similar way, even in individuals with severely atrophic jaws.